STRATEGI AGRESIF MELALUI PENGAYAAN MEDIA SOSIAL DALAM MENINGKATKAN KUALITAS PROMOSI DI DESA WISATA SARONGGE KABUPATEN CIANJUR - Indria Angger Kusuma; Nova Eviana (LPPM and Travel Operation Department Universitas Asa Indonesia, 2022)
Development of tourism village is a cross-ministry program that aims to improve community welfare and village independence. The tourism village developments actively encourage the community to identify the potential of its territory and develop its potential for tourism activities. The appropriate promotional strategy, therefore, needs to be formulated to increase the number of tourist visits. This research aims to formulate the best promotional strategy in Sarongge Tourism Village Cianjur. This research uses SWOT analysis by identifying internal factors of strengths and weaknesses and external factors of opportunities and challenges. Research data are collected through observation and interviews with managers of Sarongge tourism village. The result of the SWOT matrix shows that the position of promotional activities in Sarongge Tourism Village is in the first quadrant, meaning that Sarongge Tourism Village has the power to take advantage of current opportunities. The promotional strategy must support aggressive growth strategy by strengthening social media in terms of diversity and content, creating virtual travel products, and developing cooperation networks.